IN ACTION STRATEGY IS ABOUT FUNDAMENTALS OF CULTURE AND ART DEVELOPMENT - Ergashova Bakhtikhon Ravshanbek qizi (Journals Park Publishing, 2022)
This article provides feedback on the further development of culture and arts in the fourth priority area of the state program "Action Strategy for the five priority areas of further development of the Republic of Uzbekistan in 2017-2021" and suggestions are outlined.
Keywords: teacher-student; instrumental performance